Performance Situation Analysis on Jaipong Dance as an Oral Tradition in Desa Tanjungmekar, Karawang - Nurhasanah, E (KnE Social Sciences, 2018)
Karawang is known as the city of “Goyang Karawang”. The cultural shift in Karawang as an urban city has an impact on culture, especially Jaipong dance. This study first aims to describe the situation regarding Jaipong dance performances in the village of Tanjungmekar, Karawang. Several aspects are analyzed in situation analysis: time, place, distance, an organization of performances, participant behavior, and public response to shows. The results of the analysis found the following: first, the situation of the Jaipong dance performance, the time of the performance stage, which was the performance structure, the place was a proscenium stage, the distance between the presenters and the audience as the relation of art participants, the performance organization was chaired by a pangrawit (drummer). Second, conservation efforts in the form of Jaipong dance training for children and adults in the Padepokan Suwanda Group. In conclusion, Jaipong dance is an association medium that is formed by the people’s entertainment situation consisting of the presenter and the audience at the same time. And the necessary efforts to preserve Jaipong dance are not lost in the community of Karawang. Keywords: Jaipong dance, oral tradition, performance situation